Inorganic fiber fabric for architectural membrane materials and architectural membrane materials

Inorganic fiber fabrics with optimized Al2O3 content and structural parameters address the weaknesses of glass and alumina fiber fabrics, providing enhanced heat resistance and strength for architectural materials.

JP7623583B2Active Publication Date: 2025-01-29NITTO BOSEKI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021062614
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-01
Publication Date
2025-01-29
Estimated Expiration
2041-04-01

AI Technical Summary

Technical Problem

Conventional non-combustible sheets using glass fiber fabrics are prone to damage at high temperatures, leading to potential failure during fires, and alumina fiber fabrics, while fire-resistant, lack sufficient strength and wovenness for architectural applications.

Method used

Inorganic fiber fabrics with specific compositions and structural parameters, including Al2O3 content, yarn weights, and weaving densities, are designed to provide enhanced heat resistance and strength, ensuring they do not damage at 800°C and maintain integrity under fire conditions.

Benefits of technology

The inorganic fiber fabrics exhibit excellent heat resistance, maintaining structural integrity and strength, with tensile strengths exceeding 2000N/25mm and 3000N/25mm in vertical and horizontal directions, respectively, and are suitable for architectural applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623583000001
    Figure 0007623583000001
Patent Text Reader

Abstract

To provide an inorganic fiber fabric for construction film material and a construction film material, which are excellent in thermal failure resistance and excellent in weavability and have high aptitude for use as a construction film material.SOLUTION: Average Al2O3 content percentage At of warp constituting an inorganic fiber fabric and average Al2O3 content percentage Ay of weft constituting the inorganic fiber fabric are 17.5% by mass or higher. Mass Tt per unit length of the warp and mass Ty per unit length of the weft fall within a range of 100 to 600 g / 1000 m. Weaving density Wt of the warp and weaving density Wy of the weft fall within a range of 10.0 to 55.0 pieces / 25 mm. A ratio of Tt to Ty (Tt / Ty) falls within the range of 0.66 to 1.50. At, Ay, Tt, Ty, Wt and Wy satisfy a following formula (1): 316.5≤Wt1 / 3×Tt1 / 2 / (At / 100)+Wt1 / 3×Ty1 / 2 / (Ay / 100)≤550.0...(1)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an inorganic fiber fabric for architectural membrane materials and an architectural membrane material. [Background technology]

[0002] Conventionally, a fireproof sheet containing a glass fiber fabric and a coating resin that coats both the front and back sides of the glass fiber fabric has been known as a membrane material for buildings or structures (hereinafter referred to as architectural membrane material) (see, for example, Patent Document 1).

[0003] However, even if the conventional non-combustible sheets can be certified as non-combustible in terms of heat generation, there is a risk that the glass fiber fabric in the non-combustible sheet will be damaged when heated at high temperatures for a long period of time. Therefore, particularly when the non-combustible sheet is used as a ceiling material, there is a risk that the non-combustible sheet will fall due to damage to the glass fiber fabric in the event of a fire, and it cannot be said that the non-combustible sheet necessarily has sufficient fire resistance.

[0004] On the other hand, a refractory material containing an alumina fiber fabric is known (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-84097 A [Patent Document 2] JP 2000-331546 A Summary of the Invention [Problem to be solved by the invention]

[0006] Therefore, it is believed that by using the above-mentioned alumina fiber fabric instead of the glass fiber fabric of the conventional non-combustible sheet, a building membrane material having sufficient fire resistance can be obtained.

[0007] However, the alumina fiber fabric is inferior in weaving ability to glass fiber fabric, and a sheet material containing the alumina fiber fabric and a coating resin that covers both the front and back sides of the alumina fiber fabric has the disadvantage that it does not have sufficient strength to be used as an architectural membrane material.

[0008] The present invention aims to provide an inorganic fiber fabric for architectural membrane materials, which eliminates such inconveniences and has excellent heat breakage resistance, excellent weaving properties, and high suitability for use as architectural membrane materials, and an architectural membrane material using said inorganic fiber fabric for architectural membrane materials. [Means for solving the problem]

[0009] In order to achieve this object, the present invention provides an inorganic fiber woven fabric for architectural membrane materials, characterized in that the average Al2O3 content At of the warp yarns constituting the inorganic fiber woven fabric and the average Al2O3 content Ay of the weft yarns constituting the inorganic fiber woven fabric are each in the range of 17.5 mass% or more, the mass Tt per unit length of the warp yarns constituting the inorganic fiber woven fabric and the mass Ty per unit length of the weft yarns constituting the inorganic fiber woven fabric are each in the range of 100 to 600 g / 1000 m, the weave density Wt of the warp yarns constituting the inorganic fiber woven fabric and the weave density Wy of the weft yarns constituting the inorganic fiber woven fabric are each in the range of 10.0 to 55.0 yarns / 25 mm, the ratio of Tt to Ty (Tt / Ty) is in the range of 0.66 to 1.50, and At, Ay, Tt, Ty, Wt, and Wy satisfy the following formula (1). 316.5≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦550.0 (1)

[0010] The inorganic fiber fabric for architectural membrane materials of the present invention has At, Ay, Tt, Ty, Wt and Wy within the above ranges and further satisfies formula (1), so that it can have excellent heat breakage resistance, excellent weaving properties, and high suitability as an architectural membrane material.

[0011] Here, the term "excellent heat resistance" for inorganic fiber fabrics for architectural membrane materials means that a sample with a 10 kg weight and a diameter of 100 mm is placed in a muffle furnace, the temperature in the furnace is raised to 800°C according to the standard heating temperature curve of ISO834, and the sample is cooled in three times the time required for the temperature rise, without any damage. The term "excellent weaving property" for inorganic fiber fabrics for architectural membrane materials means that no slack, fluff, or breakage of the thread occurs during warping or weaving. The term "high suitability for architectural membrane materials" for inorganic fiber fabrics for architectural membrane materials means that a test piece cut to a width of 25 mm and a length of 150 mm in both the vertical and horizontal directions is evaluated by a tensile test conforming to JIS L 1096:2010, and the tensile strength is 2000 N / 25 mm or more.

[0012] In the inorganic fiber fabric for architectural membrane material of the present invention, it is preferable that At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (2). 346.0≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦464.0 (2)

[0013] The inorganic fiber fabric for architectural membrane materials of the present invention can have even better heat breakage resistance, excellent weaving properties, and even higher suitability as architectural membrane materials when At, Ay, Tt, Ty, Wt, and Wy satisfy formula (2).

[0014] Here, the inorganic fiber fabric for architectural membrane material has better heat breakage resistance when a sample with a 100mm diameter weight of 10kg is placed in a muffle furnace, the temperature inside the furnace is raised to 800°C so that the temperature is in line with the standard heating temperature curve of ISO834, and the temperature is lowered in three times the time required for the temperature rise, the sample is not damaged, and when a test piece is cut to a width of 25mm and a length of 150mm in both the vertical and horizontal directions and evaluated in a tensile test conforming to JIS L 1096:2010, the tensile strength is 450N / 25mm or more. Also, the inorganic fiber fabric for architectural membrane material has higher architectural membrane material suitability when a test piece is cut to a width of 25mm and a length of 150mm in both the vertical and horizontal directions and evaluated in a tensile test conforming to JIS L 1096:2010, the tensile strength is 3000N / 25mm or more.

[0015] In the inorganic fiber fabric for architectural membrane material of the present invention, it is preferable that At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (3). 316.5≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦550.0 (3)

[0016] The inorganic fiber fabric for architectural membrane materials of the present invention can have excellent heat breakage resistance, excellent weaving properties, and high suitability as architectural membrane materials because At, Ay, Tt, Ty, Wt, and Wy satisfy formula (3).

[0017] In the inorganic fiber fabric for architectural membrane material of the present invention, it is preferable that At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (4). 346.0≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦464.0 (4)

[0018] The inorganic fiber fabric for architectural membrane materials of the present invention can have even better heat breakage resistance, excellent weaving properties, and even higher suitability as architectural membrane materials when At, Ay, Tt, Ty, Wt, and Wy satisfy formula (4).

[0019] The architectural membrane material of the present invention is characterized by comprising any one of the above-mentioned inorganic fiber fabrics for architectural membrane materials, and a coating resin that coats both the front and back sides of the inorganic fiber fabric for architectural membrane materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Next, the embodiment of the present invention will be described in more detail.

[0021] In the inorganic fiber fabric for architectural membrane material of the present embodiment, the average Al2O3 content At of the warp yarns constituting the inorganic fiber fabric and the average Al2O3 content Ay of the weft yarns constituting the inorganic fiber fabric are each in the range of 17.5 mass% or more, the mass Tt per unit length of the warp yarns constituting the inorganic fiber fabric and the mass Ty per unit length of the weft yarns constituting the inorganic fiber fabric are each in the range of 100 to 600 g / 1000 m, the weave density Wt of the warp yarns constituting the inorganic fiber fabric and the weave density Wy of the weft yarns constituting the inorganic fiber fabric are each in the range of 10.0 to 55.0 yarns / 25 mm, the ratio of Tt to Ty (Tt / Ty) is in the range of 0.66 to 1.50, and the At, Ay, Tt, Ty, Wt, and Wy satisfy the following formula (1). 316.5≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦550.0 (1)

[0022] Regarding the average Al2O3 content At of the warp yarns constituting the inorganic fiber fabric and the average Al2O3 content Ay of the weft yarns constituting the inorganic fiber fabric, for example, when the warp yarns are formed by combining or twisting together n types of inorganic fiber yarns having different Al2O3 contents, the average Al2O3 content of the warp yarns can be calculated by At=ΣAti×Tti / ΣTti (where i and n are integers of 1 or more, i≦n), where Ati is the Al3O3 content (mass%) of the i-th type of inorganic fiber yarn and Tti is the mass per unit length of the i-th type of inorganic fiber yarn.

[0023] The contents of At and Ay are preferably in the range of 17.5 to 35.0 mass %, more preferably in the range of 20.5 to 30.0 mass %, and further preferably in the range of 23.5 to 28.0 mass %.

[0024] The inorganic fiber yarn may contain, for example, SiO2 in the range of 40.0 to 80.0 mass%, preferably in the range of 50.0 to 75.0 mass%, more preferably in the range of 60.0 to 70.0 mass%, further preferably in the range of 61.0 to 69.0 mass%, and particularly preferably in the range of 63.5 to 66.5 mass%, in addition to Al2O3. The inorganic fiber yarn may contain CaO and MgO in the range of 5.0 to 20.0 mass%, preferably in the range of 7.5 to 15.0 mass%, and more preferably in the range of 8.5 to 11.5 mass% in total.

[0025] The mass per unit length of the warp yarns constituting the inorganic fiber woven fabric (Tt) and the mass per unit length of the weft yarns constituting the inorganic fiber woven fabric (Ty) are preferably in the range of 136 to 540 g / 1000 m, more preferably in the range of 180 to 450 g / 1000 m, even more preferably in the range of 226 to 425 g / 1000 m, particularly preferably in the range of 250 to 420 g / 1000 m, and most preferably in the range of 256 to 350 g / 1000 m.

[0026] The weave density Wt of the warp yarns constituting the inorganic fiber woven fabric is preferably in the range of 12.0 to 36.0 yarns / 25 mm, more preferably in the range of 15.0 to 30.0 yarns / 25 mm, even more preferably in the range of 17.0 to 25.0 yarns / 25 mm, and particularly preferably in the range of 18.3 to 24.7 yarns / 25 mm. The weave density Wy of the weft yarns constituting the inorganic fiber woven fabric is preferably in the range of 12.0 to 36.0 yarns / 25 mm, more preferably in the range of 15.0 to 30.0 yarns / 25 mm, even more preferably in the range of 17.0 to 25.0 yarns / 25 mm, and particularly preferably in the range of 18.3 to 24.7 yarns / 25 mm, and most preferably in the range of 18.4 to 19.9 yarns / 25 mm.

[0027] The ratio of the Tt to the Ty (Tt / Ty) is preferably in the range of 0.75 to 1.34, more preferably in the range of 0.80 to 1.25, and further preferably in the range of 0.90 to 1.12.

[0028] The inorganic fiber yarn constituting the inorganic fiber fabric for architectural membrane materials of this embodiment is preferably a plied yarn formed by twisting together 2 to 120 identical inorganic fiber yarns, more preferably a plied yarn formed by twisting together 5 to 90 identical inorganic fiber yarns, even more preferably a plied yarn formed by twisting together 8 to 50 identical inorganic fiber yarns, and particularly preferably a plied yarn formed by twisting together 10 to 20 identical inorganic fiber yarns.

[0029] In addition, it is preferable that the inorganic fiber yarns constituting the inorganic fiber woven fabric are not subjected to bulky processing.

[0030] Examples of the inorganic fiber yarns constituting the inorganic fiber fabric for architectural membrane materials of this embodiment include glass fiber yarns, glass fiber ply yarns (ply yarns formed by twisting the same glass fiber yarns together), ceramic fiber yarns, ceramic fiber ply yarns, ply yarns of multiple types of glass fiber yarns, ply yarns of multiple types of ceramic fiber yarns, ply yarns of glass fiber yarns and ceramic fiber yarns, ply yarns of glass fiber yarns and alumina fiber yarns, and ply yarns of ceramic fiber yarns and alumina fiber yarns. Of these, glass fiber yarns or glass fiber ply yarns are preferred because of their excellent weaving properties, and glass fiber ply yarns are more preferred because of their excellent tensile strength and high suitability for architectural membrane material applications.

[0031] When the inorganic fiber yarn constituting the inorganic fiber fabric is a glass fiber yarn or a glass fiber twisted yarn, the filament diameter of the glass filament constituting the glass fiber yarn or the glass fiber twisted yarn is, for example, in the range of 2.5 to 21.0 μm, preferably in the range of 3.0 to 13.0 μm, and more preferably in the range of 3.0 to 9.0 μm.

[0032] Furthermore, when the inorganic fiber yarn constituting the inorganic fiber woven fabric is a glass fiber yarn or a glass fiber ply-twisted yarn, the number of glass filaments constituting the glass fiber yarn or the glass fiber ply-twisted yarn is, for example, in the range of 150 to 20,000, preferably in the range of 600 to 18,000, more preferably in the range of 1,000 to 15,000, even more preferably in the range of 1,500 to 10,000, particularly preferably in the range of 1,800 to 9,000, especially preferably in the range of 2,000 to 8,000, and most preferably in the range of 2,200 to 7,500.

[0033] The mass per unit area of ​​the inorganic fiber fabric for architectural membrane materials of this embodiment is, for example, 310 to 750 g / m 2 and preferably 410 to 650 g / m 2 More preferably, the range is 420 to 550 g / m 2 and particularly preferably 425 to 490 g / m 2 The range is.

[0034] Examples of the weave of the inorganic fiber fabric include plain weave, twill weave, satin weave, basket weave, and rib weave.

[0035] In the inorganic fiber fabric for architectural membrane material of this embodiment, the At, Ay, Tt, Ty, Wt and Wy preferably satisfy the following formula (2), and more preferably satisfy the following formula (5). 346.0≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦464.0 (2) 358.0≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦418.0 (5)

[0036] Furthermore, in the inorganic fiber fabric for architectural membrane materials of this embodiment, it is more preferable that At, Ay, Tt, Ty, Wt, and Wy satisfy the following formula (3), particularly preferably the following formula (4), and most preferably the following formula (6). 316.5≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦550.0 (3) 346.0≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦464.0 (4) 358.0≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦418.0 (6)

[0037] The inorganic fiber fabric for architectural membrane materials of this embodiment may have a surface treatment agent such as a silane coupling agent, starch, or lubricant adhered to its surface in a proportion of 0.3 to 2.5 mass % relative to the mass of the inorganic fiber fabric for architectural membrane materials of this embodiment including the surface treatment agent.

[0038] Examples of silane coupling agents include aminosilanes (γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N'-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, etc.), chlorosilanes (γ-chloropropyltrimethoxysilane, etc.), epoxysilanes (γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.), Examples of the silane coupling agent include silanes such as silanes (γ-mercaptotrimethoxysilane, etc.), vinylsilanes (vinyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, etc.), acrylicsilanes (γ-methacryloxypropyltrimethoxysilane, etc.), and cationic silanes (N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, N-phenyl-3-aminopropyltrimethoxysilane hydrochloride, etc.). The silane coupling agent may be used alone or in combination of two or more of these compounds.

[0039] Examples of starch include corn starch, potato starch, rice starch, tapioca starch, wheat starch, sweet potato starch, high amylose corn starch, sago starch, and starches that have been subjected to processing such as etherification, esterification, grafting, crosslinking, etc. These compounds may be used alone or in combination of two or more kinds.

[0040] Examples of lubricants include modified silicone oil, animal oil (beef tallow, etc.) and its hydrogenated products, vegetable oil (soybean oil, coconut oil, rapeseed oil, palm oil, castor oil, etc.) and its hydrogenated products, animal wax (beeswax, lanolin, etc.), vegetable wax (candelilla wax, carnauba wax, etc.), mineral wax (paraffin wax, montan wax, etc.), condensation products of higher saturated fatty acids and higher saturated alcohols (stearic acid esters such as lauryl stearate, etc.), polyethyleneimine, polyalkylpolyamine alkylamide derivatives, fatty acid amides (for example, dehydration condensation products of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, etc., and fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, etc.), and quaternary ammonium salts (alkyl trimethyl ammonium salts such as lauryl trimethyl ammonium chloride, etc.). The lubricants can be used alone or in combination of two or more types.

[0041] The architectural membrane material of this embodiment includes any one of the inorganic fiber fabrics for architectural membrane materials described above, and a coating resin that coats both the front and back sides of the inorganic fiber fabric for architectural membrane materials.

[0042] The coating resin may be a fluorine-based resin or a silicone resin. Examples of the fluorine-based resin include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-ethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), tetrafluoroethylene-perfluorodioxysol copolymer (TFE / PDD), polyvinyl fluoride (PVF), etc.

[0043] The coating resin may be a resin composition containing, in addition to a resin, an additive such as a coating agent, etc. Also, a part of the coating resin may be impregnated into the inorganic fiber fabric.

[0044] Examples of applications of the architectural membrane material of this embodiment include membrane ceilings, tent warehouses, and roofs of fire-resistant buildings.

[0045] Next, examples of the present invention and comparative examples will be described. EXAMPLES

[0046] [Example 1] The inorganic fiber fabric of Example 1 was produced by plain weaving the warp and weft yarns made of glass fiber ply-twisted yarns having a composition of 25.0 mass% Al2O3, 65.0 mass% SiO2, and 10.0 mass% combined content of MgO and CaO, and consisting of 2,400 glass filaments with a diameter of 7.4 μm and a mass of 270 g / 1,000 m, with a warp weave density of 24.6 yarns / 25 mm and a weft weave density of 19.7 yarns / 25 mm.

[0047] [Example 2] The inorganic fiber fabric of Example 2 was produced by plain weaving the warp and weft yarns made of glass fiber ply-twisted yarns having a composition of 25.0 mass% Al2O3, 65.0 mass% SiO2, and 10.0 mass% combined content of MgO and CaO, and consisting of 3,600 glass filaments with a diameter of 7.4 μm and a mass of 405 g / 1,000 m, with a warp weave density of 18.5 yarns / 25 mm and a weft weave density of 19.0 yarns / 25 mm.

[0048] [Example 3] The inorganic fiber fabric of Example 3 was produced by plain weaving the warp and weft yarns made of glass fiber ply-twisted yarns having a composition of 25.0 mass% Al2O3, 65.0 mass% SiO2, and 10.0 mass% combined content of MgO and CaO, and consisting of 1,800 glass filaments with a diameter of 7.4 μm and a mass of 202 g / 1,000 m, with a warp weave density of 24.5 yarns / 25 mm and a weft weave density of 21.0 yarns / 25 mm.

[0049] [Example 4] A first glass fiber twisted yarn having a composition with an Al2O3 content of 25.0 mass%, an SiO2 content of 65.0 mass%, a total content of MgO and CaO of 10.0 mass%, composed of 2400 glass filaments having a diameter of 7.4 μm and a mass of 270 g / 1000 m, and a second glass fiber twisted yarn having a composition with an Al2O3 content of 14.0 mass%, an SiO2 content of 54.5 mass%, a total content of MgO and CaO of 23.5 mass%, and a total content of other components of 8.0 mass%, composed of 1200 glass filaments having a diameter of 7.4 μm and a mass of 135 g / 1000 m were used as warp and weft yarns, and the warp weave density was 18.5 threads / 25 mm and the weft weave density was 19.0 threads / 25 mm. Plain weave was used to produce the inorganic fiber fabric of Example 4.

[0050] [Comparative Example 1] The inorganic fiber fabric of Comparative Example 1 was produced by plain weaving alumina fiber yarns having a composition with an Al2O3 content of 72.0 mass% and a SiO2 content of 28.0 mass% and a mass of 100 g / 1000 m as warp and weft threads, with a warp weave density of 19.8 threads / 25 mm and a weft weave density of 16.8 threads / 25 mm.

[0051] [Comparative Example 2] The inorganic fiber fabric of Comparative Example 2 was produced by plain weaving alumina fiber yarns having a composition with an Al2O3 content of 62.5 mass%, a SiO2 content of 24.5 mass%, and a total content of other components of 13.0 mass%, and a mass of 100 g / 1000 m, as warp and weft yarns, with a warp weave density of 19.8 yarns / 25 mm and a weft weave density of 16.8 yarns / 25 mm.

[0052] [Comparative Example 3] An inorganic fiber fabric of Comparative Example 3 was produced by plain weaving alumina fiber ply / twisted yarn having a composition with an Al2O3 content of 72.0 mass% and a SiO2 content of 28.0 mass% and having a mass of 300 g / 1000 m, and a glass fiber ply / twisted yarn having a glass composition with an Al2O3 content of 14.0 mass%, a SiO2 content of 54.5 mass%, a total content of MgO and CaO of 23.5 mass%, and a total content of other components of 8.0 mass%, which is composed of 1200 glass filaments with a diameter of 7.4 μm and has a mass of 135 g / 1000 m, as warp and weft yarns. The warp weave density was 17.5 threads / 25 mm and the weft weave density was 16.5 threads / 25 mm.

[0053] [Comparative Example 4] An inorganic fiber fabric of Comparative Example 4 was produced by plain weaving alumina fiber ply / twisted yarn having a composition with an Al2O3 content of 62.5 mass%, a SiO2 content of 24.5 mass%, and a total content of other components of 13.0 mass%, and having a mass of 300 g / 1000 m, and a glass fiber ply / twisted yarn having a glass composition with an Al2O3 content of 14.0 mass%, a SiO2 content of 54.5 mass%, a total content of MgO and CaO of 23.5 mass%, and a total content of other components of 8.0 mass%, which is composed of 1200 glass filaments with a diameter of 7.4 μm and has a mass of 135 g / 1000 m, as warp and weft yarns. The warp weave density was 17.5 threads / 25 mm, and the weft weave density was 16.5 threads / 25 mm.

[0054] [Comparative Example 5] A first glass fiber twisted yarn having a composition with an Al2O3 content of 25.0 mass%, a SiO2 content of 65.0 mass%, a total content of MgO and CaO of 10.0 mass%, composed of 1200 glass filaments having a diameter of 7.4 μm and having a mass of 135 g / 1000 m, and a second glass fiber twisted yarn having a composition with an Al2O3 content of 14.0 mass%, a SiO2 content of 54.5 mass%, a total content of MgO and CaO of 23.5 mass%, and a total content of other components of 8.0 mass%, composed of 2400 glass filaments having a diameter of 7.4 μm and having a mass of 270 / 1000 m were used as warp and weft yarns, and the warp weave density was 18.5 threads / 25 mm and the weft weave density was 19.0 threads / 25 mm. Plain weave was used to produce an inorganic fiber fabric of Comparative Example 5.

[0055] [Comparative Example 6] An inorganic fiber fabric of Comparative Example 6 was produced by plain weaving the warp and weft yarns made of glass fiber twisted yarns having a composition of 25.0 mass% Al2O3, 65.0 mass% SiO2, and 10.0 mass% combined content of MgO and CaO, and consisting of 1200 glass filaments with a diameter of 7.4 μm and a mass of 135 g / 1000 m, with a warp weave density of 19.0 yarns / 25 mm and a weft weave density of 18.5 yarns / 25 mm.

[0056] [Comparative Example 7] The inorganic fiber fabric of Comparative Example 7 was produced by plain weaving a warp yarn made of glass fiber twisted yarn having a composition with an Al2O3 content of 25.0 mass%, a SiO2 content of 65.0 mass%, and a total content of MgO and CaO of 10.0 mass%, which is composed of 1200 glass filaments having a diameter of 7.4 μm and has a mass of 135 g / 1000 m, and a weft yarn made of glass fiber twisted yarn having a composition with an Al2O3 content of 25.0 mass%, a SiO2 content of 65.0 mass%, and a total content of MgO and CaO of 10.0 mass%, which is composed of 3600 glass filaments having a diameter of 7.4 μm and has a mass of 405 g / 1000 m.

[0057] [Comparative Example 8] An inorganic fiber fabric of Comparative Example 8 was produced by plain weaving the warp and weft yarns made of glass fiber ply-twisted yarns having a composition of 14.0 mass% Al2O3, 54.5 mass% SiO2, 23.5 mass% combined content of MgO and CaO, and 8.0 mass% combined content of other components, and consisting of 1,780 glass filaments with a diameter of 7.4 μm and a mass of 200 g / 1,000 m, with a warp weave density of 19.8 threads / 25 mm and a weft weave density of 19.7 threads / 25 mm.

[0058] Mass per unit area of ​​the inorganic fiber fabric of each Example and Comparative Example, Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100) and (Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 The values ​​of {Ay / 100)} are shown in Table 1.

[0059] The inorganic fiber fabrics of each Example and Comparative Example were evaluated for heat breakage resistance, suitability for architectural membrane materials, and weaving properties as follows. The results are shown in Table 1.

[0060] [Heat resistance to breakage] A sample with a 100mm diameter weight of 10kg is placed in a muffle furnace, and the temperature inside the furnace is raised to 800℃ according to the standard heating temperature curve of ISO834. After cooling for three times the time required for heating, the sample is removed and checked for damage. Next, a test piece is cut into a width of 25mm and a length of 150mm in both the vertical and horizontal directions, and evaluated by a tensile test in accordance with JIS L 1096:2010. If there is no damage and the tensile strength is 450N / 25mm or more, it is rated as "A", if there is no damage and the tensile strength is less than 450N / 25mm, it is rated as "B", and if there is damage, it is rated as "C".

[0061] [Suitability for architectural membrane materials] Test pieces are cut to a width of 25 mm and a length of 150 mm in both the vertical and horizontal directions and evaluated by a tensile test in accordance with JIS L 1096:2010. A tensile strength of 3000N / 25mm or more is rated as "A", a tensile strength of 2000N / 25mm or more but less than 3000N / 25mm is rated as "B", and a tensile strength of less than 2000N / 25mm is rated as "C".

[0062] [Weavability] When warping or weft weaving is performed, if no slack, fluff or breakage of the yarn occurs, it is rated as "OK", and if slack, fluff or breakage of the yarn occurs, it is rated as "NG".

[0063] [Table 1]

[0064] It is clear from Table 1 that the inorganic fiber fabrics of Examples 1 to 4 have excellent heat breakage resistance, excellent weaving properties, and high suitability as architectural membrane materials.

[0065] On the other hand, the average Al2O3 content At of the warp yarn constituting the inorganic fiber woven fabric and the average Al2O3 content Ay of the weft yarn constituting the inorganic fiber woven fabric are higher than those of Examples 1 to 4, and Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 It is clear that the inorganic fiber fabrics of Comparative Examples 1 and 2, in which the value of / (Ay / 100) is less than 316.5, are poorly suited to be used as architectural membrane materials and have poor weaving properties.

[0066] In addition, the average Al2O3 content At of the warp yarn constituting the inorganic fiber woven fabric and the average Al2O3 content Ay of the weft yarn constituting the inorganic fiber woven fabric are lower than those of Comparative Examples 1 and 2, but Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 It is clear that the inorganic fiber fabrics of Comparative Examples 3 and 4, in which the value of / (Ay / 100) is less than 316.5, have poor weaving properties.

[0067] Also, Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 The inorganic fiber fabric of Comparative Example 5, in which the value of Wt / (Ay / 100) is more than 550.0, clearly has low heat breakage resistance. 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 The inorganic fiber fabric of Comparative Example 6, which has a value of / (Ay / 100) of less than 316.5 and is lower than the inorganic fiber fabrics of Comparative Examples 3 and 4, clearly has low heat breakage resistance and suitability as a building membrane material.

[0068] Furthermore, it is clear that the inorganic fiber woven fabric of Comparative Example 7, in which the ratio of Tt to Ty (Tt / Ty) is less than 0.66, has poor weaving properties, and it is clear that the inorganic fiber woven fabric of Comparative Example 8, in which the average Al2O3 content At of the warp yarns constituting the inorganic fiber woven fabric and the average Al2O3 content Ay of the weft yarns constituting the inorganic fiber woven fabric are less than 17.0 mass%, has low heat breakage resistance.

Claims

1. An inorganic fiber fabric for architectural membrane materials, comprising: The average Al of the warp yarns constituting the inorganic fiber woven fabric 2 O 3 The content At and the average Al of the weft yarn constituting the inorganic fiber woven fabric 2 O 3 The content Ay is in the range of 17.5 mass% or more, a mass (Tt) per unit length of a warp yarn constituting the inorganic fiber woven fabric and a mass (Ty) per unit length of a weft yarn constituting the inorganic fiber woven fabric are each in the range of 100 to 600 g / 1000 m; a weave density Wt of a warp yarn constituting the inorganic fiber woven fabric and a weave density Wy of a weft yarn constituting the inorganic fiber woven fabric are each in the range of 10.0 to 55.0 yarns / 25 mm; a ratio of the Tt to the Ty (Tt / Ty) is in the range of 0.66 to 1.50; The inorganic fiber fabric for architectural membrane materials, wherein At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (1). 316.5≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦550.0 ・・・(1)

2. 2. The inorganic fiber woven fabric for architectural membrane materials according to claim 1, wherein At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (2). 346.0≦Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)≦464.0 ・・・(2)

3. 3. The inorganic fiber woven fabric for architectural membrane materials according to claim 1 or 2, wherein At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (3). 316.5≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦550.0 ・・・(3)

4. The inorganic fiber fabric for architectural membrane materials according to any one of claims 1 to 3, characterized in that At, Ay, Tt, Ty, Wt and Wy satisfy the following formula (4). 346.0≦(Tt / Ty){Wt 1 / 3 ×Tt 1 / 2 / (At / 100)+Wy 1 / 3 ×Ty 1 / 2 / (Ay / 100)}≦464.0 ・・・(4)

5. 5. An architectural membrane material comprising the inorganic fiber fabric according to claim 1 and a coating resin that coats both the front and back sides of the inorganic fiber fabric.

Citation Information

Patent Citations

  • Fire resistant cable

    JP2000331546A

  • Glass fiber cloth for dust collection filter, and bag filter including cloth

    JP2017144430A

  • Incombustible film material and manufacturing method therefor

    JP2017159483A

  • Glass cloth composite noncombustible sheet material and building which uses it

    JP2018084097A

  • Glass fabric and glass fiber sheet material using same

    WO2013084897A1